2018
DOI: 10.1002/2017jd027522
|View full text |Cite
|
Sign up to set email alerts
|

Response of Surface Temperature to Afforestation in the Kubuqi Desert, Inner Mongolia

Abstract: In this study, micrometeorological observations in a shrub ecosystem and an adjacent poplar plantation forest ecosystem in the Kubuqi Desert, Inner Mongolia, China, are used to evaluate the theory of intrinsic biophysical mechanism (IBPM) and to investigate the biophysical effects of afforestation. Results indicate that after forcing energy balance closure to the observed fluxes, the IBPM theory agrees very well with the observed temporal variations in the surface temperature and with the observed temperature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 53 publications
4
31
1
1
Order By: Relevance
“…This study extends the work we have recently published [36]. In that study, we deployed a space-for-time strategy to investigate the T s response to afforestation.…”
Section: Introductionsupporting
confidence: 66%
See 2 more Smart Citations
“…This study extends the work we have recently published [36]. In that study, we deployed a space-for-time strategy to investigate the T s response to afforestation.…”
Section: Introductionsupporting
confidence: 66%
“…These datasets contain the daily climatological variables (the pressure, the temperature at 1.5 m, the wind at 10 m and the precipitation) for 2008 for nine meteorological stations across the Kubuqi Desert (Figure 3c, black dots). In addition, the surface flux variables (sensible heat, latent heat, ground heat) were evaluated against the data obtained in 2008 at an eddy-covariance site located in a shrubland ecosystem in the center of the Kubuqi Desert (40 Figure 3c, red dot; [36]).…”
Section: Landmentioning
confidence: 99%
See 1 more Smart Citation
“…This tight water balance between ET and precipitation found at the Beijing polar plantation site is very similar to that of Kubuqi in IM (Hao et al 2016b). A long term water balance study on water use between a planted 6 year old plantation and a native shrub land in the Kubuqi Desert (annual precipitation~320 mm) , Lu et al 2011, Wang et al 2018 found that poplar plantations used more water than was received by incident natural precipitation. The growing season ET was similar between the two sites (~220 mm), but the growing season ET at the poplar site exceeded precipitation by~80 mm, while the ET of the shrub land was similar to the precipitation, indicating that irrigation is essential to meet the poplars' ET demand.…”
Section: Unsustainability Of Large-scale Afforestation In Inner Mongoliasupporting
confidence: 51%
“…Both the IBM and TRM methods are based on the surface energy balance equation. As a result, energy balance closure is an important condition for the two models (Wang et al, ). Unfortunately, the measured fluxes do not always satisfy the surface energy balance condition and the ground heat flux or heat storage measurements are not always available.…”
Section: Discussionmentioning
confidence: 99%